Changes in pain, daily occupations, lifestyle, and health following an occupational therapy lifestyle intervention: a secondary analysis from a feasibility study in patients with chronic high-impact pain - Nielsen Svetlana Solgaard; Skou Søren T.; Larsen Anette Enemark; Polianskis Romanas; Arendt-Nielsen Lars; Østergaard Anne Skov; Kjær-Staal Petersen Kristian; Vægter Henrik Bjarke; Søndergaard Jens; Christensen Jeanette Reffstrup (Scandinavian Journal of Pain, 2023)
This study explored changes in pain-related parameters, occupational function, occupational balance, lifestyle factors, and self-perceived health status in adults with chronic high-impact pain participating in an occupational therapy lifestyle intervention.